2021
DOI: 10.3390/e23111553
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Functional Connectivity Measures for Brain Network Analysis in the Context of AD Detection with EEG

Abstract: This work addresses brain network analysis considering different clinical severity stages of cognitive dysfunction, based on resting-state electroencephalography (EEG). We use a cohort acquired in real-life clinical conditions, which contains EEG data of subjective cognitive impairment (SCI) patients, mild cognitive impairment (MCI) patients, and Alzheimer’s disease (AD) patients. We propose to exploit an epoch-based entropy measure to quantify the connectivity links in the networks. This entropy measure relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…• Node betweenness centrality (NBC): The betweenness of a node is the number of shortest paths passing through a node in a graph. It is a pointer to the influence a node has on the information flow in a graph/network (Jalili, 2016;Abazid et al, 2021). • Node strength (NS): Node strength measures the node's contribution to the entire network by taking the sum of the weights of the link and joining it to the adjacent nodes (Hata et al, 2016;Duan et al, 2020).…”
Section: Graph Theory Analysis Of Brain Networkmentioning
confidence: 99%
“…• Node betweenness centrality (NBC): The betweenness of a node is the number of shortest paths passing through a node in a graph. It is a pointer to the influence a node has on the information flow in a graph/network (Jalili, 2016;Abazid et al, 2021). • Node strength (NS): Node strength measures the node's contribution to the entire network by taking the sum of the weights of the link and joining it to the adjacent nodes (Hata et al, 2016;Duan et al, 2020).…”
Section: Graph Theory Analysis Of Brain Networkmentioning
confidence: 99%
“…Classification based on complex network topology to differentiate different types of dementia like MCI (Babiloni et al, 2004), AD (Afshari & Jalili, 2017), dementia with Lewy bodies (DLB) (van Dellen et al, 2015) and vascular dementia (VD) (Babiloni et al, 2004; Vecchio et al, 2021) are potential areas of research but not widely investigated. Support Vector Machine (SVM) algorithm with features of statistical entropy has been efficiently used for classification of subjective cognitive impairment (SCI) patients, MCI patients, and AD (Abazid et al, 2021). Further, a recent study demonstrated a fully automatic procedure based on machine learning to discriminate MCI and AD subjects (Ding et al, 2022).…”
Section: Eegdata For Connectivity Analysismentioning
confidence: 99%
“…So far limited studies were published in classification of neurological disorder using EEG signals in ensemble CNN or with other deep learning approaches. Among them classification algorithm using features derived from functional connectivity data has found success in deciphering the neurological disorder (Abazid et al, 2021; Alotaibi & Maharatna, 2021; Ding et al, 2022; Kinney‐Lang et al, 2019; van Diessen et al, 2013; Wadhera & Kakkar, 2020; Wang et al, 2022). Another major limitation for the realization of wireless EEG monitoring system would be the lack of technology infrastructure that can enable smooth transmission of data and services.…”
Section: Eegdata For Connectivity Analysismentioning
confidence: 99%
“…We show that this new framework allows conducting a refined brain network analysis, which highly contributes to a better understanding of the evolution of AD from SCI to dementia through the MCI stage. In a more recent study [ 76 ], we combined EpEn to graph theory but considered binary network analysis to discriminate automatically between SCI, MCI and AD patients (a classification problem). By contrast, the present work investigates the brain network topology over the three stages in order to retrieve global patterns that characterize the evolution towards dementia.…”
Section: Introductionmentioning
confidence: 99%